(untitled) (Indian Journal of Animal Production and Management, 2025)
Newcastle disease (ND) is caused by a virulent strain of paramyxovirus type 1 (APMV-1) infected with high morbidity and mortality, ND consider highly pathogenic disease of poultry and is caused by virulent, messogenic and lentogenic strains of Newcastle disease virus (NDV). The velogenic NDV infected poultry and cause high mortality high economic loses in poultry industry. In last year’s Broilers and layer poultry farms in Iraq suffer from high morbidity and mortality, clinically characterized by tortocalus with greenish diarrhea and sharp decrease in egg production with high morbidity and mortality, grossly characterized by ulceration in proventriculus, cecal tonsils and payer’s patches, so that this research was designed for identification of velogenic strains of NDV in Iraq. Fifteen samples (trachea, spleen and intestine) were collected from infected poultry flock after (3-5) days post clinical signs appear. The molecular methods (RT-PCR) test confirmed three samples infected with vNDV, Nucleotide sequences of vNDV were obtained from NCBI websites and alignment with other researchers concerned in this topic. The three sequencing results in this study have been submitted to the gene bank database under accession number MN901943.1, MN901944.1, and MN901945.1, phylogenetic analysis of our sequences were used to relatedness of strain obtaining with other vNDV around the world, the a current sequences of NDV strains were found to be related as a common ancestor with Iranian registered NDV.